Dam Impacts on Seasonality of Water and Sediment Transport in Intensively Managed River Basins: A Case Study of the Yangtze River. Issue 11 (15th November 2022) - Tian, Q.; Xu, K. H.; Wang, Y. P.; Liang, C. J.
Abstract: Extensive studies have been performed on water and sediment transport of the Yangtze River in recent decades, but very few studies were focused on seasonal and daily variations. After the construction of Three Gorges Dam (TGD) in 2003, several key cascade dams were built on the Yangtze upstream. Annual, monthly, and daily data were used to study the seasonality change on water level, water discharge, and sediment load in response to multiple reservoir impoundments. TGD impacted the water level inside the reservoir greatly by shifting the peak water level from summer to winter and made the hydrograph more asymmetrical. In contrast, minor changes in water levels (<2 m) occurred at stations downstream of the TGD mainly due to channel incision. Downstream of TGD at Yichang station, annual hydrograph was flattened slightly: water discharge in the dry season increased 49% whereas that of flood season decreased 14% from 1956–2002 to 2013–2017. Mean annual water discharge downstream of the TGD was slightly impacted because the impounded water was <5% of annual inflow of the reservoir. Comparing with the Yangtze, the annual hydrographs of other intensively managed rivers like the Yellow, Missouri, and Colorado have been flattened more effectively by reservoir impoundments. The sediment rating curves at Yichang and Hankou changed from an oval‐like shape before 2013 to two overlapping and flattened lines in 2013–2017. This shift indicates that the rising and falling limbs of the hydrograph experienced similar sediment concentrations in 2013–2017 and suggests a less obvious hysteresis effect. Over 50% of the sediment load observed at the seaward‐most Datong station was contributed by the large tributaries in the upper reach, like Jinsha and Jialing rivers, before 2003. The channel scour downstream of TGD contributed 49%–64% of the Datong sediment load after 2003. Plain Language Summary: Cascade dams were built on the Yangtze River mainstream, including the largest and key dams and reservoirs in China, like the Three Gorges Dam (TGD) in 2003. Annual, monthly, and daily data were used to study the seasonality change on water level, water discharge, and sediment load in response to multiple reservoir impoundments. The seasonality of water level in Three Gorges Reservoir does not follow the natural hydrological cycle in the river basin anymore. Rapid rising and slow falling in reservoir water level are mainly controlled by rapid impoundment and slow water release during hydropower generation. In contrast, minor changes in water levels (<2 m) occurred at stations downstream of the TGD mainly due to channel incision. Mean annual water discharge downstream of the TGD was slightly impacted because the impounded water was <5% of annual inflow of the reservoir. Comparing with the Yangtze, the annual hydrographs of other intensively managed rivers like the Yellow, Missouri, and Colorado Rivers have been more effectively flattened by reservoir impoundments. Our findings are valuable to water and sediment management of other large rivers that are experiencing increasing anthropogenic impacts. Key Points: Impoundment shifted the peak water level inside the Three Gorges Reservoir from summer to winter and changed the hydrograph to be asymmetrical Rating curves of water discharge versus sediment load at Yichang and Hankou changed from an oval‐like shape before 2013 to two overlapping and flattened lines in 2013–2017 Comparing with the Yangtze, the annual hydrographs of the Yellow, Missouri, and Colorado Rivers have been flattened more effectively by reservoir impoundments